2021
DOI: 10.7554/elife.59529
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of the microtubule network self-organization in epithelia

Abstract: Robustness of biological systems is crucial for their survival, however, for many systems its origin is an open question. Here we analyze one sub-cellular level system, the microtubule cytoskeleton. Microtubules self-organize into a network, along which cellular components are delivered to their biologically relevant locations. While the dynamics of individual microtubules is sensitive to the organism's environment and genetics, a similar sensitivity of the overall network would result in pathologies. Our larg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 75 publications
2
8
0
Order By: Relevance
“…MTSD correlated with cell elongation ( Figure 5C )—more elongated cells with higher eccentricities had a steeper distribution (smaller MTSD) that reflected more aligned microtubules, with no significant difference between the two regions of the pupal wing examined. Such correlation of the microtubule angle distribution with the cell eccentricity agrees with the reported robustness of microtubule alignment with each other in subapical microtubule networks of epithelial cells ( Płochocka et al. , 2021 ).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…MTSD correlated with cell elongation ( Figure 5C )—more elongated cells with higher eccentricities had a steeper distribution (smaller MTSD) that reflected more aligned microtubules, with no significant difference between the two regions of the pupal wing examined. Such correlation of the microtubule angle distribution with the cell eccentricity agrees with the reported robustness of microtubule alignment with each other in subapical microtubule networks of epithelial cells ( Płochocka et al. , 2021 ).…”
Section: Resultssupporting
confidence: 88%
“…The localization of the minus ends in noncentrosomal networks is of particular interest, as it ensures the correct polarized transport by motor proteins ( Steinhauer and Kalderon, 2006 ; Zhelezov et al. , 2019 ).To examine the possibility that Ft-Ds complexes alter the distribution of the minus ends without affecting the overall organization of subapical microtubules, we turned to the minus-end capping protein Patronin, which localizes at apical junctions and exhibits an asymmetrical distribution in the Drosophila embryonic epidermis that depends on the cell elongation ( Goodwin and Vale, 2010 ; Płochocka et al. , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because microtubule disorganization has been demonstrated to impair the membrane recruitment of cell junction proteins ( 49 , 50 ), we extracted the membrane and cytosolic fractions of Caco-2 monolayer cultures and determined the distribution of cell junction proteins in each fraction. Immunoblot analysis showed that treating the cells with purified Bc-5 alveolysin or with wild-type Bc-5 cells, but not alveolysin mutant Bc-5 cells (Δ4211Δ5613), significantly decreased the membrane accumulation of ZO-1, claudin-4, and E-cadherin (Fig.…”
Section: Resultsmentioning
confidence: 99%